HUBUNGAN PEMBERIAN SUSU FORMULA DAN CARA PENGGUNAAN BOTOL SUSU DENGAN KEJADIAN DIARE PADA BALITA - Mariani, Andi; Fauzan, Fauzan; Nuliana, Wa; Susanti, Ni Made Dewi; Zakiah, Siti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Based on an initial survey, it is known that diarrhea cases have increased at Puskesmas Tambang in 2023. Cases of diarrhea in toddlers can be caused by various factors such as the environment, consumption of formula milk and how to use a milk bottle. The purpose of the study was to determine the relationship between formula milk feeding and how to use milk bottles with the incidence of diarrhea in toddlers. The type of research is quantitative with a cross sectional design. The research was conducted in 2023 at Puskesmas Tambang. The research sample amounted to 41 people. The research instrument used a research questionnaire. The results showed there was a relationship between formula feeding (p value: 0.002) and how to use milk bottles (p value: 0.001) with the incidence of diarrhea in toddlers. It is recommended to parents to always follow posyandu activities and actively seek information so that parents know how to use milk bottles appropriately so that toddlers avoid diarrhea.Keywords: Toddler, Diarrhea, Formula Milk